Forestry Spatial Planning Policy Direction: Concerning the Long-Term National Development Plan 2025-2045 - Belinda Arunarwati Margono; Judin Purwanto; Sigit Nugroho (Jurnal Ilmu Kehutanan, 2025)
The role of forests is related to the challenges of balancing food, water, and energy, which are likely to increase significantly in the near future. A science-based conception is needed to support the correct application of forest adequacy in terms of forestland and forest cover over a watershed or island to address these challenges and to strengthen the role of forests in performing economic, social, and ecological functions, mainly in the context of water, food, and energy security. However, the minimum extent of forest over land is still debatable. The determination of what is named forest adequacy, in terms of both forestland (kawasan hutan) and forest cover (penutupan hutan), needs to consider roles of biogeophysical factors, environmental carrying capacity, watershed characteristics, along with flora and fauna diversity. Spatial planning plays a crucial role in implementing the concept of determining the forest's adequacy based on spatial considerations to support the Forestry Spatial Planning Policy in the 2025-2045 National Development Plan to ensure the future security of water, food, and energy supply.